PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN BAHASA INDONESIA KELAS VIII DI SMP NEGERI 5 KOTA BENGKULU - Intan Anggriani; khermarinah; Randi (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to determine the effect of the Inquiry learning model on student achievement in Indonesian language in eighth grade at SMP Negeri 5, Bengkulu City, consisting of two classes. This study is categorized as a quantitative quasi-experimental study using the "matching-only pretest-posttest control group design." The first group (class VIII A) was given treatment (the experimental group), and the second group (class VIII C) was not given treatment (the control group). This model was supported by data collection techniques, observation, testing (pretest and posttest), and documentation. Based on the posttest results, the average score of the experimental class increased from 57.4 to 83.2, while the control class increased from 58.8 to 72.6. From these results, it can be concluded that the average score of the experimental class increased significantly compared to the control class. Furthermore, statistical tests were conducted using SPSS 27 to determine whether the hypothesis was rejected or accepted. The results of the T-test revealed a t-value of 4.520 with a significance level of 0.000. Therefore, it can be concluded that the HO is rejected and the HI is accepted, as 0.000 is less than 0.025. This indicates a significant difference between the experimental and control classes in terms of learning outcomes.